Local Government Response in Corona Pandemic: An Overview of Karnali Province - Shahi, Min Bahadur; Devkota, Chiranjivi (Research Nepal Journal of Development Studies, 2022)
The world was completely locked down for the first time in the world by the devastating pandemic of coronavirus in 2020. To overview its impacts on service delivery of local governments of Karnali province of Nepal, the study has been conducted. the paper attempts to explore the local government initiatives and inter-governmental coordination toward the COVID-19 response during the first wave. The study is based on a descriptive qualitative research design to reach the set objectives. Three local governments of Karnali Province were selected purposively as samples. Questionnaire and telephonic interviews were the tools adopted for the data collection. The field-level information and data were presented as per the objectives in a descriptive way. The study has been made to draw conclusions based on the practical experience and information gained from all three local levels. Local governments have been seen to be at the forefront of coping with the uncomfortable situation created by the Novel Corona Virus pandemic. Similarly, the local government seems to have performed important tasks such as manpower mobilization, procurement of health-related materials, test kits and machines, swab collection and test, and awareness rising toward covid-19 response and rescue of returnees from abroad. The local governments have found utilized the available resources for creating, managing the quarantine, and isolation at the community level to control the Covid-19. The local governments have learned the lessons from the field-level experiences in the pandemic management process in such types of crises. The study would be helpful to share the pandemic management knowledge among the local governments in the future.